The Era of The Smartphone: Technological Progress and Online Security - Marcin STRZELEC; Ewa MAŁACHOWSKA (Communications of International Proceedings, 2022)
The scientific progress and development and use of new information and communication technologies have led to the emergence of new threats. Living in the modern-day world is becoming more and more connected with technology, which may also mean that conflict situations and violence have moved from the real word to the virtual world. Universal access to mobile phones with constant online connectivity has not only changed the character of communication, but also spread negative phenomena, including violence. A new phenomenon of cyberbullying has emerged. Performed with the use of technology, in particularly the Internet, by an individual or a group of people, this behaviour involves sending multiple aggressive messages or other similar actions intended to do harm. An analysis of studies into this area shows the need to promote a strategy of effective prevention and psycho-educational intervention.
Keywords: Internet; smartphone; communicators; security; cyberbullying.